Production Of Precipitated Calcium Carbonate (PCC) Using Malaysian Limestone Based Materials Via Continuous Production Technique - Ismail, Roniza (2010)

(untitled)
In present commercial practice, precipitated calcium carbonate (PCC) is normally manufactured by reacting the „milk of lime‟ with carbon dioxide (CO2) in a stirred tank batch reactor system. The drawback of this technique is PCC could not be produced uninterrupted for the required quantity in a real time process continuously. Thus, two newly designed lab scale reactors i.e. tall tubular and sprayed-mist are used in this study to produce PCC in continuous mode. The main aim is to investigate the operating variables that control the PCC synthesis using these continuous techniques as well as to evaluate the properties of the resulted PCC.